Impairment of Vα24-Jα18+Vβ11+ natural killer T cells in adult acute lymphoblastic leukemia patients - Zhao, Haijun; Li, Zhifeng; Xie, Shiting; Luo, Yiming; Zhou, Yong; Deng, Manman; Zeng, Hanyan; Zhao, Jintao; Yu, Lian; Xu, Bing (Experimental cell research, 2019)
Type I natural killer T (NKT) cells are attractive candidates for cancer immunotherapy. In this study, we examined the characteristics of type I NKT cells in patients with adult B-cell acute lymphoblastic leukemia (ALL). We first identified type I NKT cells as Vα24-Jα18 and Vβ11 double-positive CD3+ lymphocytes. Using this method, we found that the adult B-cell ALL patients presented significantly lower level of type I NKT cells than the age- and sex-matching control subjects. The expression of IL-21 by type I NKT cells was then examined using intracellular flow cytometry, which showed that with α-GalCer stimulation, the adult B-cell ALL patients presented significantly lower level of IL-21+ type I NKT cells than control subjects. By both flow cytometry and ELISA, we found that the vast majority of IL-21-expressing type I NKT cells expressed IL-21R, which was also reduced in adult B-cell ALL patients. Using an in vitro co-culture system, we demonstrated that IL-21R+, but not IL-21R-, type I NKT cells could promote the IFN-γ, granzyme B, and perforin expression by CD8 T cells in an IL-21-dependent fashion. This type I NKT cell-mediated stimulatory effect was reduced in adult B-cell ALL patients than in control subjects. In addition, we observed a positive correlation between the frequency of IL-21R+ type I NKT cells and the frequencies of IFN-γ-, granzyme B-, and perforin-expressing circulating CD8 T cells in adult B-cell ALL patients directly ex vivo. Overall, this study identified an IL-21-related impairment in type I NKT cells from adult B-cell ALL patients. •Type I NKT cell frequency was significantly reduced in adult B-cell ALL patients.•Type I NKT cells from adult B-cell ALL patients showed lower IL-21 and IL-21R levels.•IL-21R+ NKT cells in ALL showed reduced capacity to promote CD8 T cell responses.•IL-21R+ type I NKT cell-mediated effects required IL-21 release.•IL-21R+ NKT cell was correlated with effector CD8 T cell frequency in ALL patients.